Intra‐epithelial non‐canonical Activin A signaling safeguards prostate progenitor quiescence. (7th March 2022) - Cambuli, Francesco; Foletto, Veronica; Alaimo, Alessandro; De Felice, Dario; Gandolfi, Francesco; Palumbieri, Maria Dilia; Zaffagni, Michela; Genovesi, Sacha; Lorenzoni, Marco; Celotti, Martina; Bertossio, Emiliana; Mazzero, Giosuè; et al.
Abstract: The healthy prostate is a relatively quiescent tissue. Yet, prostate epithelium overgrowth is a common condition during aging, associated with urinary dysfunction and tumorigenesis. For over thirty years, TGF‐β ligands have been known to induce cytostasis in a variety of epithelia, but the intracellular pathway mediating this signal in the prostate, and its relevance for quiescence, have remained elusive. Here, using mouse prostate organoids to model epithelial progenitors, we find that intra‐epithelial non‐canonical Activin A signaling inhibits cell proliferation in a Smad‐independent manner. Mechanistically, Activin A triggers Tak1 and p38 ΜAPK activity, leading to p16 and p21 nuclear import. Spontaneous evasion from this quiescent state occurs upon prolonged culture, due to reduced Activin A secretion, a condition associated with DNA replication stress and aneuploidy. Organoids capable to escape quiescence in vitro are also able to implant with increased frequency into immunocompetent mice. This study demonstrates that non‐canonical Activin A signaling safeguards epithelial quiescence in the healthy prostate, with potential implications for the understanding of cancer initiation, and the development of therapies targeting quiescent tumor progenitors. Synopsis: Non‐canonical Activin A signalling in the prostate inhibits cell proliferation in a Smad‐independent manner and safeguards epithelial quiescence. This represents a key molecular mechanism controlling prostate quiescence, with implications for benign prostate hyperplasia and tumorigenesis. Activin A signalling inhibits prostate progenitor proliferation through a non‐canonical pathway mediated by Tak1/p38. Activin A triggers Tak1 and p38 ΜAPK activity, leading to p16 and p21 nuclear import. Reduced Activin A signalling is associated with DNA replication stress and aneuploidy in 3D organoids. Dysregulation of the pathway leads to dysplastic growth in an orthotopic transplantation mouse model. Abstract : Non‐canonical Activin A signalling in the prostate inhibits cell proliferation in a Smad‐independent manner and safeguards epithelial quiescence. This represents a key molecular mechanism controlling prostate quiescence, with implications for benign prostate hyperplasia and tumorigenesis.